114 Reducing Barriers to Learning With eBooks: An Internationally Accessible and Affordable Resource. (4th May 2021) - Ellis, R
Abstract: Introduction: Training in Urology is often limited at an undergraduate level, especially in the wake of the COVID-19 pandemic. It is not uncommon that a trainee's first experience of Urology is when they encounter urological patients as a clinician and studies have revealed that graduates are lacking knowledge and confidence in managing urological pathology. Many trainees across the world are unable to access vital learning resources to address this gap in knowledge due to exorbitant prices set by publishing companies. Method: To address the need for affordable standardised education, 'Urology for Medical Students and Junior Doctors' was created. This self-published eBook was written and peer-reviewed by urologists to create a relevant learning resource that is affordable for all. Results: Over 1000 copies of the eBook were downloaded in the first 90 days after publication by trainees across the world. It has been downloaded internationally by a diverse range of allied healthcare professionals. All profits generated from sales are donated to charities investing in medical education. Conclusions: This eBook stands as an example of how we as educationalists and clinicians can produce affordable learning resources for trainees worldwide; standardising training, improving patient safety and reducing barriers to learning.